INTRODUCING ECOLOGICAL ISLAMIC BOARDING SCHOOL - Inayatul Maula; Zainuddin; Muhammad Solehuddin (Jurnal Pendidikan Islam, 2021)
AbstractThe idea of ecological boarding school is actually not a new idea in the of Islamic boarding school. Islamic boarding schools as the oldest educational institutions in Indonesia are already familiar with ecological studies, both in the fields of interpretation of the Qur'an, Hadith, Fiqh, and the yellow book which become the basis of their knowledge. However, it is still theoretical and has not yet fully implemented. This study uses library research in the form of searching the latest books, books and journals. This paper concludes that it is time for Islamic boarding schools to transform their scientific treasures, especially those related to ecology, into a real movement. Islamic boarding schools must return to their identity as agents of social change by utilizing the scientific treasures, their community and human resources they have by creating ecological boarding schools.